2020
DOI: 10.1093/mnras/staa2015
|View full text |Cite
|
Sign up to set email alerts
|

The formation of ultradiffuse galaxies in the RomulusC galaxy cluster simulation

Abstract: We study the origins of 122 ultra-diffuse galaxies (UDGs) in the RomulusC zoom-in cosmological simulation of a galaxy cluster (M200 = 1.15 × 1014 M⊙), one of the only such simulations capable of resolving the evolution and structure of dwarf galaxies (M⋆ < 109 M⊙). We find broad agreement with observed cluster UDGs and predict that they are not separate from the overall cluster dwarf population. UDGs in cluster environments form primarily from dwarf galaxies that experienced early cluster in-fall and su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 135 publications
4
90
0
Order By: Relevance
“…10 Gyr) can be neglected when a galaxy has a massive dark matter halo. However, numerical simulations 33 suggest that a dark matter halo will be gradually stripped by tidal interactions with other galaxy cluster members during flybys, which would cause the overall stellar disc expansion by about 25% over 10 Gyr. Assuming passive evolution, based on best-fitting stellar population parameters and a slow disc expansion, we can predict internal properties (luminosity, surface brightness, luminosity-and mass-weighted stellar metallicities) of our galaxies up-to 10 Gyr from now (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…10 Gyr) can be neglected when a galaxy has a massive dark matter halo. However, numerical simulations 33 suggest that a dark matter halo will be gradually stripped by tidal interactions with other galaxy cluster members during flybys, which would cause the overall stellar disc expansion by about 25% over 10 Gyr. Assuming passive evolution, based on best-fitting stellar population parameters and a slow disc expansion, we can predict internal properties (luminosity, surface brightness, luminosity-and mass-weighted stellar metallicities) of our galaxies up-to 10 Gyr from now (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…As extremes in the relationship between galaxy size and luminosity, LSBGs provide a litmus test for models that predict galaxy properties from cosmological principles (e.g., Ferrero et al 2012;Papastergis et al 2015). It has been suggested that LSBGs form naturally within the ΛCDM framework, either primordially in halos with high angular velocity (Dalcanton et al 1997;Amorisco & Loeb 2016) or through evolution in dense environments (Tremmel et al 2020;Martin et al 2019). On the other hand, observations of LSBGs with anomalously low dark matter content (van Dokkum et al 2018(van Dokkum et al , 2019 may necessitate modified models of galaxy formation (e.g., Papastergis et al 2017;Sales et al 2020) and/ or dark matter physics (e.g., Carleton et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…• The initial UDG studies suggested that UDGs represent a population of failed galaxies that assembled their dark matter haloes and were rapidly quenched at high redshift due to environmental processes in galaxy clusters, mainly ram pressure stripping (van Dokkum et al 2015a;Koda et al 2015;Yozin & Bekki 2015;Benavides et al 2021). Additionally, as a consequence of the passive evolution of their stellar populations, UDGs surface brightness have decreased with time (Román & Trujillo 2017;Román et al 2019;Tremmel et al 2020). This scenario is consistent with observations of cluster UDGs as gas-poor (Karunakaran et al 2020;Chen et al 2020) quiescent (Singh et al 2019), old, metal-poor, and alpha-enhanced (Kadowaki et al 2017;Gu et al 2018;Pandya et al 2018;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018).…”
Section: Introductionmentioning
confidence: 99%